(untitled) (Journal of the College of Basic Education, 2024)
The current research aims to impart directing skills to students at the Institute of Fine Arts in shadow theater. The research problem was identified as a weakness among the students. The study included fourth-year theater department students at the Institute of Fine Arts who are studying the subject of theatrical directing. The researcher adopted the experimental method, using the experimental design of two equivalent groups—experimental and control—with a post-test. A research tool was designed and validated for reliability and consistency. After teaching according to the cyclical inquiry model and using appropriate statistical methods, it was found that there is a significant effect of teaching using this model on increasing student achievement. Consequently, the researcher organized the scientific material in this modest study by outlining the research problem and its importance.The current research aims to explore the effect of the cyclical inquiry model on imparting directing skills to students at the Institute of Fine Arts in shadow theater. The first chapter represents the general framework of the research, including the research problem, its importance, and the boundaries defined by the students of the fourth-year theater department who study theatrical directing. It also includes the definition of the terms mentioned in the research title The second chapter covers the theoretical framework, representing constructivist theory, skills, the cyclical inquiry model, directing skills, shadow theater, and previous studies along with their discussion. The third chapter presents the research methodology and procedures, including the appropriate experimental design, defining the research population, selecting and homogenizing the sample, ensuring equivalence between the experimental and control groups, controlling variables, constructing research tools, and applying the experiment along with the suitable statistical methods.In the fourth chapter, it was concluded that the cyclical inquiry model significantly impacts the acquisition of directing skills among fourth-year students at the Institute of Fine Arts studying theatrical directing. This chapter also includes conclusions, recommendations, and references